Quo Vadis Peran IMF bagi Perekonomian Indonesia - Suharto - (Universitas Islam Indonesia, 2003)
International Monetary Fund (IMF) that built on December 31, 1945 until now has developed its member. The aim of IMF as written article 1 of articles agreement of international monetary fund. In long term development perspective, the changing of paradigm that guaranteed the justice. Indonesia has a rich natural resources but Indonesian can not expiore their natural resources. If Indonesian can explore their natural resources. Indonesia will become a welfare state without IMF. According to author of this writing that the principle of justice must become a main basic either in construct ing or decision of economy strategy in Indonesia in the future.